Genetic diversity of Orientia tsutsugamushi strains circulating in Northeast India. (2nd March 2018) - Bora, Trishna; Khan, Siraj Ahmed; Jampa, Lobsang; Laskar, Basanta
Abstract: Background: Scrub typhus, caused by the intracellular bacteria Orientia tsutsugamushi is widely distributed in Southeast Asian countries with antigenically divergent strains reported across the Asia–Pacific belt. The present study was conducted to characterize the circulating strains of Orientia tsutsugamushi prevailing in two Northeastern states of India—the gateway to most Southeast Asian countries. Methods: A total of 278 (98 clinical and 180 field collected) scrub typhus positive blood samples collected from December 2014 to December 2016 were subjected for amplification of partial 56 KDa, 47 KDa and 16SrRNA genes of Orientia . Results: Highest number of PCR positives were obtained for 56 KDa gene (17.3%); followed by 11.2% for 47 KDa gene and 5.1% for 16S rRNA gene. High degree of genetic diversity was identified among the identified strains, especially within the 56 KDa gene. Different strains of Orientia circulate in the northeastern part of India, with a pre-dominance of Karp-like strains. Independently branched isolates formed distinct clades, suggesting the possibility of a new strain type of Orientia . Conclusion: This study provides insight into the genetic and evolutionary relationship of Orientia strains prevalent in this part of the country. Understanding the regional genetic diversity is crucial for its implications in vaccine developments strategies as well as sero-diagnostics. Accession numbers: KU163366, KY594249, KY594248, KY594251, KU163359, KU163361, KU163363, KU163369, KY594250, KP067915, KU163373, KU163372, KU163370, KU163364, KU163362, KY594247, KY594252, KU163360, KU163365, KU163367, KU163368, KU163371, KX1555826, KY594257, KY594255, KY594256, KX155825, KX155829, KX155827, KX155828, KY594254, KY594253, KY594258, KY583503, KY583499, KY583501, KY583500, KY583502